Comprehensive Physiology 2015
DOI: 10.1002/cphy.c140078
|View full text |Cite
|
Sign up to set email alerts
|

Liver Sinusoidal Endothelial Cells

Abstract: The liver sinusoidal endothelial cell (LSEC) forms the fenestrated wall of the hepatic sinusoid and functions as a control post regulating and surveying the trafficking of molecules and cells between the liver parenchyma and the blood. The cell acts as a scavenger cell responsible for removal of potential dangerous macromolecules from blood, and is increasingly acknowledged as an important player in liver immunity. This review provides an update of the major functions of the LSEC, including its role in plasma … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
285
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 231 publications
(285 citation statements)
references
References 278 publications
(454 reference statements)
0
285
0
Order By: Relevance
“…However, accumulating evidence has reconfirmed the uptake of denatured proteins, vital staining dyes, and small particles by the hepatic sinusoidal endothelium and lymph node reticular cells (18,31). It is generally accepted that hepatic sinusoidal endothelial cells play a pivotal role in the clearance of bloodborn waste macromolecules and particles by receptor-mediated endocytosis, whereas large particles are phagocytosed by Kupffer cells (37). Most researchers have not paid attention to the uptake of exogenous particles in the endothelium of the lung, adrenal gland, and heart, where we demonstrated the selective expression of LYVE-1 in the present study.…”
Section: Topographical and Functional Relationship Between Lyve-1-expmentioning
confidence: 99%
See 1 more Smart Citation
“…However, accumulating evidence has reconfirmed the uptake of denatured proteins, vital staining dyes, and small particles by the hepatic sinusoidal endothelium and lymph node reticular cells (18,31). It is generally accepted that hepatic sinusoidal endothelial cells play a pivotal role in the clearance of bloodborn waste macromolecules and particles by receptor-mediated endocytosis, whereas large particles are phagocytosed by Kupffer cells (37). Most researchers have not paid attention to the uptake of exogenous particles in the endothelium of the lung, adrenal gland, and heart, where we demonstrated the selective expression of LYVE-1 in the present study.…”
Section: Topographical and Functional Relationship Between Lyve-1-expmentioning
confidence: 99%
“…It has been shown that endothelial cells-especially hepatic sinusoidal endothelial cells, a representative RES member-comprise an important part of the innate immune system for eliminating foreign particles from the circulation. Smedsrød and his colleagues (32,36,37) have termed the endocytic endothelial cells as scavenger endothelial cells, leading us to resurrect the concept of the RES (39). A weak point in this effort to re-evaluate the RES is the lack of marker substances that can specify the RES members.…”
mentioning
confidence: 99%
“…Sinusoidal fenestration is known to disappear with age and negatively impacts liver function. 22 We performed RIPC on old mice and prepared liver immediately after the last RIPC cycle for electron microscopy. Although liver of shamtreated mice had typical signs of pseudocapillarization, fenestration in sinusoids of RIPC-treated mice was enlarged and more regular (Fig.…”
Section: Ripc Mitigates Age-related Deficiencies In Hepatic Sinusoidsmentioning
confidence: 99%
“…1,2) The unique permeable structure provided by LSECs enables plasma to freely access to the disse space (which is the space between LSECs and hepatocytes), whereby hepatocytes can exchange small molecules (like nutrients) without directly contacting the blood stream.…”
mentioning
confidence: 99%